Proteoglycans and neuronal migration in the cerebral cortex during development and disease - Maeda, Nobuaki (Frontiers in Neuroscience, 2015)
Chondroitin sulfate proteoglycans and heparan sulfate proteoglycans are major constituents of the extracellular matrix and the cell surface in the brain. Proteoglycans bind with many proteins including growth factors, chemokines, axon guidance molecules, and cell adhesion molecules through both the glycosaminoglycan and the core protein portions. The functions of proteoglycans are flexibly regulated due to the structural variability of glycosaminoglycans, which are generated by multiple glycosaminoglycan synthesis and modifying enzymes. Neuronal cell surface proteoglycans such as PTPzeta, neuroglycan C and syndecan-3 function as direct receptors for heparin-binding growth factors that induce neuronal migration. The lectican family, secreted chondroitin sulfate proteoglycans, forms large aggregates with hyaluronic acid and tenascins, in which many signaling molecules and enzymes including matrix proteases are preserved. In the developing cerebrum, secreted chondroitin sulfate proteoglycans such as neurocan, versican and phosphacan are richly expressed in the areas that are strategically important for neuronal migration such as the striatum, marginal zone, subplate and subventricular zone in the neocortex. These proteoglycans may anchor various attractive and/or repulsive cues, regulating the migration routes of inhibitory neurons. Recent studies demonstrated that the genes encoding proteoglycan core proteins and glycosaminoglycan synthesis and modifying　enzymes are associated with various psychiatric and intellectual disorders, which may be related to the defects of neuronal migration.